2019
DOI: 10.2471/blt.18.221572
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of a community-led sanitation campaign in India, 2005–2016

Abstract: Objective To evaluate the long-term impact of a community-led total sanitation campaign in rural India. Methods Local organizations in Odisha state, India worked with researchers to evaluate a community-led total sanitation campaign, which aimed to increase the demand for household latrines by raising awareness of the social costs of poor sanitation. The intervention ran from February to March 2006 in 20 randomly-selected villages and 20 control villages. Within sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
1
22
1
2
Order By: Relevance
“…For example, several studies find that a relatively high fraction of households owning latrines have members that do not use them (Barnard et al, 2013;Cameron et al, 2013, Orgill-Meyer et al, 2019. Other studies report an increase over time in open defecation rates (Crocker et al, 2017a) and latrine abandonment (Orgill-Meyer et al, 2019). Based on these findings, our analysis assumes that all households that build a latrine use and maintain it for 5 years, and that a fixed percentage of households abandon their latrine in each of the subsequent 5 years.…”
Section: Overviewmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, several studies find that a relatively high fraction of households owning latrines have members that do not use them (Barnard et al, 2013;Cameron et al, 2013, Orgill-Meyer et al, 2019. Other studies report an increase over time in open defecation rates (Crocker et al, 2017a) and latrine abandonment (Orgill-Meyer et al, 2019). Based on these findings, our analysis assumes that all households that build a latrine use and maintain it for 5 years, and that a fixed percentage of households abandon their latrine in each of the subsequent 5 years.…”
Section: Overviewmentioning
confidence: 93%
“…Operations and maintenance costs depend on the extent to which members of households with latrines actually use them, which evidence suggests declines over time. For example, several studies find that a relatively high fraction of households owning latrines have members that do not use them (Barnard et al, 2013;Cameron et al, 2013, Orgill-Meyer et al, 2019. Other studies report an increase over time in open defecation rates (Crocker et al, 2017a) and latrine abandonment (Orgill-Meyer et al, 2019).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanations for the poor performance of sanitation assert that sanitation has been a low priority for both donors and national policy-makers, resulting in low levels of investment and poor capacity in the sector. At the country level, evidence of these shortcomings is most evident in examples of toilet abandonment and reversion to open defecation (Hueso & Bell 2013;Improve International 2014;Orgill-Meyer et al 2019), what Kwiringira et al (2014) describe as 'descending the sanitation ladder'.…”
Section: Introductionmentioning
confidence: 99%
“…One notable exception to this is research in the state of Odisha in India, which revealed that despite a sustained sanitation behaviour change campaign and the availability of public funds for toilet construction, a huge number of toilets built under the Community-Led Total Sanitation Campaign were abandoned within a decade. The analysis of data from Odisha suggested that a lack of durable maintenance arrangements and a failure to stimulate and sustain demand resulted in only short-term reductions in open defecation (Orgill-Meyer et al 2019). Similarly, research in Uganda highlighted capacity and resources challenges for the maintenance and upkeep of communal sanitation facilities, leading to toilet misuse, abandonment, and the continuation of open defecation (Kwiringira et al 2014).…”
Section: Introductionmentioning
confidence: 99%